M*A*S*H. Season seven [videorecording (DVD)] - Metcalfe, Burt; Alda, Alan, 1936-; Swit, Loretta; Morgan, Harry, 1915-2011; Gelbart, Larry (20th Century Fox Home Entertainment, 2004)
More adventures for the doctors and nurses of the 4077th unit during the Korean War. Includes all 26 episodes from the 7th season, 1978-1979.